Acute and long-term effects of electroacupuncture alter frontal and insular cortex activity and functional connectivity during resting state. (30th April 2020) - Ren, Yuanyuan; Xu, Mingzhu; von Deneen, Karen M.; He, Yang; Li, Guanya; Zheng, Yang; Zhang, Wenjing; Li, Xiaoping; Han, Yu; Cui, Guangbin; Ji, Gang; Nie, Yongzhan; et al.
Highlights: Electroacupuncture (EA) significantly decreased body mass index. EA increased resting brain activity in ventrolateral prefrontal cortex. EA induced increased positive functional connectivity between VLPFC and OFC. EA induced increased negative functional connectivity between VLPFC and THA. Functional changes in frontal/insular cortex are related to EA-induced weight-loss. Abstract: Electroacupuncture (EA) is a safe method for treating obesity; however, its underlying neural mechanisms remain unclear. We employed resting-state-functional-magnetic-resonance-imaging (RS-fMRI) and amplitude-of-low-frequency-fluctuation (ALFF) to investigate acute/long-term effects of EA on brain activity and resting-state-functional-connectivity (RSFC) in overweight/obesity subjects who received real/Sham stimulation. For acute effects, 26 and 19 overweight/obesity subjects were included in EA and Sham groups respectively. There were significant time effects on ALFF in the right insula (INS) and left dorsolateral-prefrontal-cortex (DLPFC) due to decreases/increases in INS/DLPFC in both groups. There were weaker positive RSFC between INS and supplementary-motor-area (SMA)/right DLPFC and weaker negative RSFC between INS and precuneus (PCUN); stronger negative RSFC between DLPFC and dorsomedial-prefrontal-cortex (DMPFC) in both groups. For long-term study, body-mass-index (BMI) had significant reduction in EA ( n  = 17) and Sham (15) groups; EA had higher BMI reduction than in Sham. There were significant time effects on ALFF in right ventrolateral-prefrontal-cortex (VLPFC) due to significant increases in EA group, and stronger positive RSFC between VLPFC and orbitofrontal-cortex and negative RSFC between VLPFC and left thalamus (THA) in both groups after long-term treatment. These findings suggest that changes in resting-activity and RSFC implicated in inhibitory-control, gastric-motility and satiety-control are associated with EA-induced weight-loss.